Contribution of parental social support and self-control to student truancy behavior - Candra Prasiska Rahmat; Herman Nirwana; Netrawati Netrawati (RedWhite Press, 2020)
This study aims to analyze the contribution of parental social support and self-control both individually and collectively on student truancy behavior. This research uses descriptive correlational quantitative method. The study population was vocational high school students Muhammadiyah 1 Padang registered in the odd semester of the school year 2020/2021 as many as 447 students. The research sample was 127 students, who were selected by purposive sampling technique. The instrument uses a parental social support scale, self-control scale and the results of student absenteeism recapitulation. The research data were analyzed using descriptive correlational statistics and multiple regressions. The research findings proved that parental social support and self-control simultaneously contributed to student truancy behavior as much as 44.5%. The implication of the results of this study can be used as input for creating guidance and counseling service programs in preventing and reducing truancy in students.